Merekonstruksi Sosok Pangeran Kuningan dalam Sejarah Cirebon - Idan Dandi; Tendi Tendi (IAIN Syekh Nurjati Cirebon, 2022)
Sunan Maulana Jati is one of the figures who spread Islam in West Java as well as the legendary ruler of Cirebon. This character has several wives who gave birth to a number of sons and daughters. One of them is Prince Kuningan who was born to his wife, Princess Ong Tien. This article aims to reconstruct the figure of Prince Kuningan who has an important role in the history and development of the Cirebon region, but due to certain political interests his name is not widely known by the people of Cirebon. This research is a qualitative research conducted with historical research methods. The source collection technique used is library research by tracing existing sources from various books or scientific articles and oral traditions that develop in the community. These various data are then verified with strict internal and external criticism in order to produce more reliable data. After being analyzed and interpreted, the results are then written in the historiography stage. This study shows that Prince Kuningan was an important figure who played a role in the development of the military and the Cirebon region. He is the son of Sunan Maulana Jati Cirebon and has the opportunity to be his successor in occupying the Cirebon leadership chair. However, the political constellations that occurred in the palace's internal side even marginalized Prince Kuningan and later drowned his name so that it was rarely discussed other than in proportion which only came from certain oral stories.